PENDIDIKAN SEKSUAL SEJAK DINI PADA ANAK - Rachmawati, Dian; Nurhidayah, S. Psi., M.Si, Siti (DEVOSI, 2020)
Sexual education is a clear and correct information regarding the issue of human sexuality which includes knowledge of conception, pregnancy, and the birth of sexual behavior which is properly given and related to the norms prevailing in society. This Community Service aims to provide knowledge for children to know personal areas that must be protected from others and children can protect themselves from the crimes that are around them by refusing from behaviors that are not liked by children such as saying "no", â€œdonâ€™tâ€ and "please". The results of the activities held in the form of teaching sexual education from an early age to children at the Raudhatul Athfal Islamic Kindergarten, the children know the areas of their private bodies that should not be touched by others except themselves, fathers, and mothers and children can reject the behavior disliked by children. Children can point out which areas of the body are not allowed by others and tell who can touch them.